Which vaginal douching agent is the best choice before oocyte retrieval? A systematic review and network meta-analysis - Meng, Ying; Wen, Gui H.; Luo, Hong; Tan, Xiu C.; Wang, Li; Liao, Juan; Peng, Hong; Lan, Ling; Yang, Na; Zhao, Ying (Frontiers in Reproductive Health, 2022)
Objective The aim of this study was to evaluate six vaginal douching agents (Iodine, Saline, Iodine followed by saline, chlorhexidine acetate followed by saline, Ozone, Potassium permanganate) on oocytes pick-up related pelvic infection (OPU-PI) and IVF outcome in patients underwent assisted reproduction technology (ART). Design Through searching PubMed, Embase, Cochrane Library, Web of Science, Ovid, CINAHL CNKI, only human clinical trials were collected to study the effects of the six vaginal douching agents on OPU-PI and IVF outcomes. The included studies were evaluated for methodological quality by the Cochrane bias risk assessment tool, and the data analysis software was used to analyze the data accordingly. Results The clinical trials were collected between the earliest available date and June 2022. Eight studies were included, the total sample size used in the study was 12,567. The results of the network meta-analysis showed that Ozone can significantly decrease OPU-PI; Iodine followed by saline can be a antiseptic protocol ranked first without affecting the quality of oocytes and Chlorhexidine acetate followed by saline can improve patients' clinical pregnancy rate. Conclusion Based on Ranking Plot of the Network, this review reports the best evidence available regarding different vaginal douching agents used before OPU.